Pembinaan Generasi Qur'ani Berbasis Moderasi Beragama di TPQ Al Amir Gintungan Tengaran - Munir, Muhammad Syaiful; Qaddafi, Faqih Jauahr; Hayati, Nafisa; Putriningtiyas, Okta; Milla, Vina Uswatun (IAIN Kendari, 2025)
The service activity in the form of building a Quranic generation has the aim of increasing the young generation's love for the Al-Qur’an at TPQ Al-Amir Gintungan. The process begins with learning by providing full assistance to students. Then, proceed with providing full assistance during the learning process. After everything is finished, an evaluation will be held to find out deficiencies during the teaching process. The teaching carried out at TPQ Al-Amir is sima'an, deposit, reading law, prophet stories, and questions and answers. Then a TPQ competition was also held to enliven the month of August. The result of this service is that after carrying out the activities that have been planned, students can have the enthusiasm to always read the Al-Qur’an and memorize it.